ANALISIS PERMODELAN BANJIR DAN PERENCANAAN RUTE EVAKUASI WILAYAH ADMINISTRASI DESA KARANGWUNI MENGGUNAKAN SISTEM INFORMASI GEOGRAFI - Bayu Pamungkas, Deni; Rohsulina, Pranichayudha; MS Khabibur Rahman; Bayu Kurniaaji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Geographic Information Systems (GIS) have been widely applied in disaster modeling analyses, including flood modeling in the administrative area of Karangwuni Village, Weru Subdistrict, Sukoharjo Regency, Central Java. This study aims to analyze flood hazard levels and to develop effective evacuation routes within Karangwuni Village using a GIS-based approach. The analysis was conducted through flood modeling using a buffer analysis method with two water level scenarios, namely 10 meters and 20 meters, to identify the extent and spatial distribution of inundation affecting residential areas, agricultural land, and road networks. Furthermore, evacuation route planning was carried out using network analysis by considering road network connectivity, travel distance, and the avoidance of road segments located within high-inundation zones. The results indicate that an increase in water level from 10 meters to 20 meters leads to a significant expansion of inundated areas, particularly in lowland zones along river corridors, which directly affects the accessibility of local road networks. The optimal evacuation routes are not necessarily the shortest in geometric distance, but rather those with lower flood exposure and more stable accessibility. These findings highlight that the integration of GIS-based flood modeling and road network analysis provides a robust spatial foundation for flood mitigation planning and for enhancing community preparedness in flood-prone areas.